Feasibility of High-Resolution Computed Tomography Imaging for Obtaining Ear Impressions for Hearing Aid Fitting. (October 2019) - Chen, Chin-Kuo; Hsieh, Li-Chun; Chiang, Yuan-Chuan; Cheng, Wei-De
Objective: This study investigated the feasibility of obtaining ear impressions for hearing aids by using 3-dimensional high-resolution computed tomography (HRCT) images. Study Design: Case series. Setting: One referral tertiary center. Subjects and Methods: Hearing-impaired adults who were fitted with 1 or 2 behind-the-ear hearing aid(s) and had undergone temporal bone HRCT for various ear pathologies were enrolled in this study. Earmolds were fabricated from the impressions obtained using the conventional ear canal silicone injection technique and the HRCT reconstructed technique. Outer ear canal resonance frequencies and amplitude in open ears and those measured with silicon and HRCT reconstructed earmolds were determined through real-ear gain measurements, including real-ear unaided gain (REUG) and real-ear occluded gain (REOG), for comparison. Results: A total of 50 HRCT reconstructed earmolds were compared with 50 conventional silicon injection earmolds. The average value of open ear canal resonance amplitude (REUG) for each ear was 0.41 to 16.76 dB. No statistically significant difference in resonance amplitude (REOG) was observed between silicon and reconstructed earmolds (paired t test, P > .05). The mean insertion loss (REOG-REUG) at all frequencies also did not differ significantly between the two earmolds (paired t test, P > .05). Conclusion: According to our real-ear measurements, acoustic characteristics of the HRCT reconstructed earmolds were compatible with those of the silicone injection earmolds. Despite concerns about increased cost and radiation exposure, the HRCT reconstructed technique is a clinically useful and applicable method and can reduce potential safety complications for difficult cases.